Indirect effect of neem oil on Podisus nigrispinus (Hemiptera, Pentatomidae): biology and predatory capacity - Campos, Aniele Pianoscki De [UNESP]; Boiça Junior, Arlindo Leal [UNESP]; Ribeiro, Zulene Antonio [UNESP] (Universidade Federal de Viçosa, 2014)
This study evaluated the effects on the development and predatory capacity of Podisus nigrispinus fed on Spodoptera frugiperda that have ingested different concentrations of neem oil. The predatory capacity of Podisus nigrispinus was assessed, separating nymphs (fourth instar) and adults (males and females). The treatments consisted of S. frugiperda larvae reared in neem oil aqueous solutions (0.077, 0.359 and 0.599%), deltamethrin EC 25 (0.100%) and control arranged in a completely randomized design, with ten replicates. Insects were offered three larval densities (one, three and six), in the third or fourth instars. The predated larvae were examined at 24 and 48 hours after the beginning of the experiment. Biological parameters of Podisus nigrispinus were evaluated in groups of ten second-instar nymphs transferred to pots, in five replicates. Insects were offered 2-6 third and/or fourth-instar larvae reared in the same neem oil concentrations in a completely randomized design. The following parameters were evaluated: duration of each nymph stage (days), nymph mortality (%), weight of fifth-instar nymphs (mg), sex ratio, weight of males and females (mg) and longevity of unfed adults (days). The predatory capacity of nymphs and adults of Podisus nigrispinus was influenced by the neem oil at the concentrations of 0.359% and 0.599% in the highest density. The concentration of 0.359% lengthened the nymphal stage and the concentration of 0.599% reduced the weight of males.

Este trabalho estudou os efeitos do óleo de nim no desenvolvimento e na capacidade predatória de Podisus nigrispinus, alimentados com lagartas de Spodoptera frugiperda, submetidas a concentrações de óleo de nim. A capacidade predatória de P. nigrispinus foi avaliada, individualizando-se ninfas (quarto ínstar) e adultos (machos e fêmeas), constando de dez repetições, sendo os tratamentos lagartas de S. frugiperda criadas nas soluções aquosas de óleo de nim (0,077 , 0,359 e 0,599%), deltametrina 25 CE (0,100%) e testemunha, em delineamento inteiramente casualizado. Foram ofertadas aos insetos três densidades de lagartas (uma, três e seis), de terceiro ou quarto ínstares. Avaliaram-se as lagartas predadas às 24 e às 48 horas do início do ensaio. Na biologia de P. nigrispinus, ninfas de segundo ínstar foram transferidas, em grupo de dez, para potes, repetidos cinco vezes. Diariamente, foram oferecidas de 2 a 6 lagartas de terceiro e,ou, quarto ínstares, criadas nas mesmas concentrações de teste, em mesmo delineamento estatístico, sendo as avaliações: duração (dias) de cada estádio ninfal, mortalidade ninfal (%), peso (mg) de ninfas no quinto ínstar, razão sexual, peso (mg) de machos e fêmeas e longevidade (dias) dos adultos sem alimento. A capacidade predatória de ninfas e adultos de P. nigrispinus foi influenciada pelo óleo de nim, na maior densidade estudada, nas concentrações de 0,359 e 0,599%. A concentração de 0,359% alongou o período ninfal e a concentração de 0,599% ocasionou menores pesos de machos.
Efeito indireto do óleo de nim sobre Podisus nigrispinus (Hemiptera, Pentatomidae): biologia e capacidade predatória
Keywords: spined soldier bug; fall armyworm; biological control; integrated pest management; botanical insecticide; percevejo predador; lagarta-do-cartucho; controle biológico; manejo integrado de pragas; inseticida botânico